The impact of service personal values on continuance intention towards on-demand ridesharing services - Aw, Eugene Cheng Xi; Kamal Basha, Norazlyn; Ng, Siew Imm (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Competition in the on-demand ridesharing service industry is becoming increasingly intense, and sustainability of this innovative business model is uncertain. Studying service personal values may provide insight for service providers to implement appropriate customer retention strategies. Therefore, the objectives of this study was to validate a structural model where service personal values influence perceived value, and perceived value acts as the predictor of satisfaction, which in turn, affects customers’ continuance intention. Through a purposive sampling technique, 280 questionnaires were collected from respondents with experience using on-demand ridesharing services in Malaysia. The findings revealed that service personal values influenced perceived value, perceived value influenced satisfaction, and satisfaction influenced continuance intention. Furthermore, perceived value mediated the relationship between service personal values and satisfaction. Implications and future research directions were discussed.